Investigating the N-Shaped Energy-Environmental Kuznets Curve Hypothesis in Saudi Arabia - Mahmood, Haider; Tanveer, Muhammad; Furqan, Maham (International Journal of Energy Economics and Policy, 2021)
The Environmental Kuznets Curve (EKC) is extensively investigated in the literature, but testing of energy-EKC is scarce in the literature. The testing of energy-EKC is very important for extensive nonrenewable energy users. This research investigated the energy and growth cubic relationship in Saudi Arabia to verify the N-shaped energy EKC from 1970-2019. The estimated long-run parameters of linear, quadratic, and cubic terms of economic growth are found positive, negative, and positive, respectively. Hence, energy-EKC is corroborated in Saudi Arabia in the long run with the first turning point of N-curve at Gross Domestic Product (GDP) per capita of 19277 constant US dollar and the second point at 30880. Hence, the increasing GDP per capita before 19277 and after 30880 would increase energy use and have environmental consequences. The increasing GDP per capita between 19277 and 30880 would decrease energy consumption and is pleasant for the environment. The same behavior of energy usage is found in the short run. Hence, the energy-EKC is also validated in the short run. Keywords: The energy EKC, energy consumption, economic growth, cointegration JEL Classifications: Q42, O44, C22 DOI: https://doi.org/10.32479/ijeep.11573